0727 Understanding Sleep and Activity in Patients Discharged from the Hospital. (27th April 2018) - Kessler, R; Shah, M; Anderson, S; Meltzer, D; Mokhlesi, B; Knutson, K; Arora, V
Abstract: Introduction: While hospitalization is associated with acute sleep loss, it is generally assumed patients recover with their return home. To date, no study has used rigorous objective methods to describe how sleep and activity levels vary post-discharge in older patients discharged from a general medicine ward. Methods: Eligible patients were over 50 years old, discharged home, community dwelling, ambulatory, and without an ICU stay or known sleep disorder. Patients wore a wrist accelerometer for at least one in-hospital night and one post-discharge night, including intervening days, providing objective measurements of sleep duration (minutes), sleep efficiency (% time asleep/ time in bed), and daytime physical activity (average activity counts/ minute). Random effect linear regression models clustered by subject were used to test associations between sleep and activity parameters during and after hospitalization and variation across days of the study from hospitalization through post-discharge. Results: From October 2012 to November 2017, 404 nights (27% in-hospital, 73% post-discharge) and 384 days (28% in-hospital, 72% post-discharge) were recorded from 54 patients. Mean nights per person were 2.1 ± 1.3 nights in-hospital and 5.4 ± 2.1 nights post-discharge. Mean days per person were 2.0 ± 1.2 days in-hospital and 5.1 ± 1.9 days post-discharge. Most patients were African American (79.3%) and female (59.3%). Average in-hospital and post-discharge sleep duration were 331.8 ± 118.5 minutes and 328.6 ± 129.5 minutes, respectively. Average in-hospital and post-discharge sleep efficiency were 74.2 ± 16.6% and 68.8 ± 21.0%, respectively. In multivariable regression models clustered by subject, neither sleep duration nor sleep efficiency increased from hospitalization through post-discharge (1.2 minutes, 95% CI [-2.6, 4.9], p=0.5; -.5%, 95% CI [-1.1, .1], p=0.1). Daytime physical activity, however, did increase from hospitalization through post-discharge (9.6 counts/minute, 95% CI [6.9, 12.3], p<0.01). Conclusion: Although hospitalization is associated with acute sleep loss, patients had neither increased sleep duration nor improved sleep efficiency post-discharge. However activity levels did improve. It is important to investigate whether patient sleep is eventually restored after discharge or if hospitalization is associated with chronic sleep disorders. Future research on how sleep and activity trajectories could predict patient outcomes is warranted. Support (If Any): K24 HL136859/NHLBI.